A Model for economic empowerment and strengthening of fishing communities in Sumenep Regency's The Archipelagic Region - Sadik Jakfar; Rahman Hairul; Wijayanto Andri (BIO Web of Conferences)
The aim of the research “A Model of Economic Empowerment and Strengthening of Fishing Communities in Sumenep Regency's Archipelagic Region” is to compile: 1) a model for empowering and strengthening the fishermen’s economy through optimizing fisheries resource management using an institutional system approach, and 2) an action plan and implementation plan for an optimal and sustainable model for empowering and strengthening the fishermen’s economy in the archipelagic region of Sumenep Regency. This research's methods and findings are: (a) finding a grand strategy for fisheries-based business development, (b) analysis of the hierarchical structure of fisheries-based business development, the result of this analysis is a fisheries-based business development policy structure model that recommends a program to strengthen the fishing community’s economy, (c) performance-importance analysis (PIA), namely measuring the capacity and performance of policies that have been implemented for the development of fisheries-based businesses, then being able to see the institutional gap between policy needs and the capacity and performance of policies that have been implemented, and (d) analyzing the aspirations of the communities and interested parties through the Focus Group Discussion (FGD) method. This research is expected to contribute to the development of regional planning science, especially local economic development.